Low-smoke high-temperature-resistant polyolefin sheath high-voltage cable and preparation method thereof

CN122968042APending Publication Date: 2026-10-23WUHAN HUANGHE NO 1 ELECTRIC WIRE & CABLE FACTORY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611133987.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但勃姆石本质为刚性无机填料,即便经过有机改性优化界面结合,其刚性颗粒引入聚乙烯基体后,仍会破坏聚乙烯连续的柔性高分子链网络,易在填料-基体界面处形成应力集中点,在外力作用下诱发微裂纹萌生与扩展,最终造成聚乙烯基复合材料的韧性与抗冲击性能劣化

Benefits of technology

1.本发明的低烟耐高温聚烯烃护套高压电缆,通过改性低密度聚乙烯母粒和改性高密度聚乙烯母粒共挤出,分别作为绝缘层和护套层,改性高密度聚乙烯母粒高于改性低密度聚乙烯母粒的结晶度,因此冷却收缩率更大,共挤冷却时,护套层的收缩量大于内层绝缘层,会在绝缘层表面产生一个均匀的径向抱紧力,使界面剥离强度提高,解决电缆在弯曲、拖拽过程中容易出现的层间脱层问题,并且该过程中,绝缘层中含有ADP/勃姆石核壳粉末,能够发挥滚珠效应,通过滑移分散应力,提高熔体流动性,维持高压电缆的冲击强度,大幅改善高压电缆的加工挤出性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968042A_ABST
    Figure CN122968042A_ABST
Patent Text Reader

Abstract

The application discloses a low-smoke high-temperature-resistant polyolefin sheath high-voltage cable and a preparation method thereof, and belongs to the technical field of power cable manufacturing. The modified low-density polyethylene master batch and the modified high-density polyethylene master batch are co-extruded to be respectively used as an insulation layer and a sheath layer. The crystallinity of the modified high-density polyethylene master batch is higher than that of the modified low-density polyethylene master batch, and therefore, the cooling shrinkage is larger. When being cooled, the shrinkage of the sheath layer is larger than that of the inner insulation layer, and a uniform radial holding force is generated on the surface of the insulation layer, so that the interface peeling strength is improved, the interlayer delamination problem of the cable which is prone to occur in the bending and dragging process is solved, and in the process, the ADP / boehmite core-shell powder contained in the insulation layer can play a ball bearing effect, disperse stress through sliding, improve the melt flowability, maintain the impact strength of the high-voltage cable, and greatly improve the processing extrusion performance of the high-voltage cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of power cable manufacturing technology, specifically a low-smoke, high-temperature resistant polyolefin sheathed high-voltage cable and its preparation method. Background Technology

[0002] High-voltage cables are core equipment in power systems for long-distance power transmission and grid interconnection. They are widely used in important scenarios such as urban main power grids, rail transit, new energy power plants (wind power, photovoltaic), large industrial plants, high-rise buildings, and underground utility tunnels. As the power industry develops towards higher voltage, larger capacity, and more intensive operation, and as environmental and safety regulations become increasingly stringent, the service environment of high-voltage cables is becoming more complex. This places higher demands on the comprehensive performance of their sheath materials. They must not only possess excellent insulation, mechanical strength, and resistance to environmental aging, but also meet the core indicators of low smoke, halogen-free, and high temperature resistance to meet safety requirements under extreme conditions such as fires and high-temperature operation.

[0003] Currently, high-voltage cable sheath materials are mainly divided into two categories: traditional materials and modified polyolefin materials. Traditional sheath materials are mainly polyvinyl chloride, ordinary polyethylene, and rubber, which have many performance shortcomings that are difficult to overcome: Although PVC sheaths are inexpensive and easy to process, they release a large amount of dense smoke and toxic and harmful gases such as hydrogen halides when burned. This not only easily leads to asphyxiation of people at the fire scene, but also corrodes electrical equipment and metal components, which does not conform to modern environmental protection and safety trends, and has been gradually restricted in its use; Ordinary PE sheaths have poor high-temperature resistance, and the long-term operating temperature can only be maintained at 70-90℃, while the conductor temperature of high-voltage cables can reach 90-105℃ when running at full load. After the heat is conducted to the sheath, it is easy to cause the material to soften and deform, accelerate thermal aging, and even become brittle and fall off, seriously affecting the insulation performance and service life of the cable.

[0004] Chinese patent announcement CN118652489B discloses a low-smoke, halogen-free, flame-retardant polyolefin-sheathed power cable. This design uses boehmite as a flame-retardant functional filler. Organic surface modification controls the surface polarity of the boehmite particles, effectively improving the interfacial compatibility between the inorganic filler and the non-polar polyethylene matrix, thus alleviating the filler agglomeration problem. However, boehmite is inherently a rigid inorganic filler. Even after organic modification to optimize interfacial bonding, the rigid particles introduced into the polyethylene matrix still disrupt the continuous flexible polymer chain network of polyethylene, easily forming stress concentration points at the filler-matrix interface. Under external force, this induces the initiation and propagation of microcracks, ultimately deteriorating the toughness and impact resistance of the polyethylene composite material. Summary of the Invention

[0005] The purpose of this invention is to provide a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable and its preparation method. The method involves co-extruding modified low-density polyethylene masterbatch and modified high-density polyethylene masterbatch, which serve as the insulation layer and sheath layer, respectively. The modified high-density polyethylene masterbatch has a higher crystallinity than the modified low-density polyethylene masterbatch, resulting in a greater cooling shrinkage rate. During co-extrusion cooling, the shrinkage of the sheath layer is greater than that of the inner insulation layer, generating a uniform radial clamping force on the surface of the insulation layer. This improves the interfacial peel strength and solves the problem of interlayer delamination that easily occurs during cable bending and dragging. Furthermore, the insulation layer contains ADP / boehmite core-shell powder, which can exert a ball-bearing effect, dispersing stress through slippage, improving melt flowability, maintaining the impact strength of the high-voltage cable, and significantly improving the processing and extrusion performance of the high-voltage cable.

[0006] The objective of this invention can be achieved through the following technical solutions: A low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable has a structure consisting of, from the inside out, conductor core, shielding layer, insulation layer, and sheath layer.

[0007] A method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable includes the following steps: Step 1: A poly(hydroxyethyl methacrylate) coating layer is formed on the surface of ADP powder by in-situ polymerization using reverse emulsion polymerization to obtain modified ADP powder. Using 4,4'-diphenylmethane diisocyanate as a bridge, prepolymerized modified ADP and prepolymerized modified boehmite are prepared by addition reaction of isocyanate groups and hydroxyl groups respectively. Then, through 1,4-butanediol chain extension reaction, boehmite is covalently bonded to the surface of modified ADP powder through polyurethane segments to obtain ADP / boehmite core-shell powder.

[0008] Step 2: Low-density polyethylene, ADP / boehmite core-shell powder, ethylene bis-stearamide and core filler are melt-blended, extruded and granulated to prepare modified low-density polyethylene masterbatch; nickel-based MOF is prepared by hydrothermal synthesis and then melt-blended with maleic anhydride-grafted high-density polyethylene, ethylene bis-stearamide and sheath filler, extruded and granulated to prepare modified high-density polyethylene masterbatch.

[0009] Step 3: Using semi-conductive shielding material as the shielding layer, modified low-density polyethylene masterbatch as the insulation layer, and modified high-density polyethylene masterbatch as the sheath layer, a three-layer co-extrusion process is adopted with the conductor core to achieve a tight, gapless wrapping of the insulation layer, sheath layer, and conductor, resulting in a low-smoke, high-temperature resistant polyolefin sheathed high-voltage cable.

[0010] Furthermore, the specific preparation steps for modified ADP powder are as follows: ADP powder, hydroxyethyl methacrylate, and ethylene glycol dimethacrylate were added to a reaction vessel and stirred for 20-30 minutes at 20-25°C and 500-600 rpm. Then, Tween-80 and Span-80 were added, and the mixture was heated to 70-80°C and stirred for another 10-12 minutes to form an oil phase mixture. Sodium dodecylbenzenesulfonate and deionized water were added to the reaction vessel and stirred for 20-30 minutes at 70-75°C and 500-600 rpm. Then, the oil phase mixture and azobisisobutyronitrile were added, and the mixture was stirred for another 4-5 hours. The mixture was centrifuged at 1000-1200 rpm for 4-6 minutes, filtered, and the product was washed 2-4 times with deionized water and dried under vacuum at 60-70°C for 1-2 hours to obtain modified ADP powder.

[0011] Furthermore, the mass ratio of ADP powder, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, Tween-80, and Span-80 is 10-12:3-5:0.5-0.7:0.4-0.6:1.2-1.5.

[0012] Furthermore, the ratio of sodium dodecylbenzenesulfonate, deionized water, oil phase mixture and azobisisobutyronitrile is 0.2-0.5g: 250-300mL: 15-16g: 0.15-0.2g.

[0013] Furthermore, the specific preparation steps for prepolymerized modified ADP are as follows: Modified ADP powder, 4,4'-diphenylmethane diisocyanate, and dibutyltin dilaurate were added to a reactor at a mass ratio of 8-10:30-40:0.05-0.07. The mixture was stirred for 20-30 minutes under a nitrogen atmosphere, at 20-25°C and 500-600 r / min. The mixture was then heated to 80-90°C and stirred for another 2-4 hours to obtain prepolymerized modified ADP.

[0014] Furthermore, the specific preparation steps for prepolymerized modified boehmite are as follows: Boehmite, 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate were added to a reactor in a mass ratio of 6-8:14-18:0.02-0.04. The mixture was heated to 80-90°C under a nitrogen atmosphere and stirred for 2-4 hours to obtain prepolymerized modified boehmite.

[0015] Furthermore, the specific preparation steps for ADP / boehmite core-shell powder are as follows: Prepolymerized modified ADP, prepolymerized modified boehmite, and 1,4'-butanediol were added to a reactor at a mass ratio of 6-8:4-6:2-4 and subjected to chain extension reaction at 80-90℃ and 500-600 r / min for 2-3 h. After filtration, the product was washed 2-4 times with deionized water and dried under vacuum at 60-70℃ for 1-2 h to obtain ADP / boehmite core-shell powder.

[0016] Furthermore, the specific preparation steps of nickel-based MOFs are as follows: Nickel nitrate, 2,5-dihydroxyterephthalic acid, and N,N-dimethylformamide were added to a polytetrafluoroethylene hydrothermal reactor and stirred at 120-130℃ and 500-600 r / min for 10-12 h. After the reaction was completed, the mixture was centrifuged at 5000-6000 r / min for 5-8 min. The precipitate was washed 2-4 times with N,N-dimethylformamide and anhydrous ethanol, respectively, and then dried under vacuum at 60-70℃ for 1-2 h to obtain nickel-based MOF.

[0017] Furthermore, the ratio of nickel nitrate, 2,5-dihydroxyterephthalic acid, and N,N-dimethylformamide is 18-20g: 12-15g: 800-900mL.

[0018] Furthermore, the specific preparation steps for modified low-density polyethylene masterbatch are as follows: Low-density polyethylene, ADP / boehmite core-shell powder, ethylene bis-stearamide and wire core filler are mixed evenly and then fed into a co-rotating parallel twin-screw extruder. The mixture is extruded at 180-185℃ and 180-190 r / min and granulated to obtain modified low-density polyethylene masterbatch.

[0019] Furthermore, the mass ratio of low-density polyethylene, ADP / boehmite core-shell powder, ethylene bis-stearamide, and core filler is 70-80:10-15:1-2:5.5-8.4.

[0020] Furthermore, the specific preparation steps of the modified high-density polyethylene masterbatch are as follows: Maleic anhydride-grafted high-density polyethylene, nickel-based MOF, ethylene bis-stearamide, and sheath filler are mixed evenly and then added to a co-rotating parallel twin-screw extruder. The mixture is extruded at 180-185℃ and 180-190 r / min, and granulated to obtain modified high-density polyethylene masterbatch.

[0021] Furthermore, the mass ratio of maleic anhydride-grafted high-density polyethylene, nickel-based MOF, ethylene bis-stearamide, and sheath filler is 70-80:10-12:1-2:22.5-31.

[0022] Furthermore, the specific steps for preparing the conductor core are as follows: Annealed soft copper monofilaments are concentrically stranded on a frame-type stranding machine or a tubular stranding machine at a pitch ratio of 14-18 to obtain the conductor core.

[0023] The beneficial effects of this invention are: 1. The low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable of the present invention is constructed by co-extruding modified low-density polyethylene masterbatch and modified high-density polyethylene masterbatch as the insulation layer and sheath layer, respectively. The modified high-density polyethylene masterbatch has a higher crystallinity than the modified low-density polyethylene masterbatch, resulting in a greater cooling shrinkage rate. During co-extrusion cooling, the shrinkage of the sheath layer is greater than that of the inner insulation layer, generating a uniform radial clamping force on the surface of the insulation layer. This improves the interfacial peel strength and solves the problem of interlayer delamination that easily occurs during cable bending and dragging. Furthermore, the insulation layer contains ADP / boehmite core-shell powder, which can exert a ball effect, disperse stress through slippage, improve melt fluidity, maintain the impact strength of the high-voltage cable, and significantly improve the processing and extrusion performance of the high-voltage cable.

[0024] 2. The ADP / boehmite core-shell powder of the present invention forms a dense poly(hydroxyethyl methacrylate) coating layer by in-situ polymerization of hydroxyethyl methacrylate on the surface of ADP. This effectively reduces the hygroscopicity of ADP and solves the problems of flame retardant performance degradation, insufficient processing stability and electrical performance deterioration caused by its easy absorption of moisture. The residual hydroxyl groups in the coating layer are combined with the inherent hydroxyl groups on the surface of boehmite and undergo a covalent reaction with isocyanate groups. Polyurethane segments are used as covalent bond bridges to construct a stable core-shell structure with ADP as the core and boehmite as the shell. This core-shell structure fully leverages the flame-retardant and smoke-suppressing effects of ADP and the physical barrier and char-reinforcing properties of boehmite, while effectively maintaining the mechanical strength of the insulation and sheath of high-voltage cables. This avoids material embrittlement and decreased mechanical properties caused by the addition of traditional flame retardants. Furthermore, the polyurethane segments and the polyethylene matrix have excellent compatibility, which can significantly inhibit the agglomeration of ADP / boehmite core-shell powder during melt processing and use, ensuring the uniformity of material processing and flame-retardant properties. At the same time, the polyurethane segments and the boehmite shell form a double barrier, which can effectively prevent ADP from migrating and precipitating onto the sheath surface, avoiding surface whitening and decreased flame-retardant durability caused by precipitation, and improving the long-term operational reliability of high-voltage cables.

[0025] 3. The sheath layer of this invention contains nickel-based MOF, and the polar groups of maleic anhydride can form hydrogen bonds with the hydroxyl groups on the surface of the nickel-based MOF, which can significantly improve the dispersibility of the nickel-based MOF in the polyethylene matrix and prevent agglomeration. The nickel ions in the nickel-based MOF act as highly efficient Lewis acid catalysts, which can promote the dehydrogenation and cross-linking reaction of the polyethylene matrix, enabling the polyethylene to quickly form a dense char layer in the early stage of combustion, reducing the release of combustible gases, and its porous nature can adsorb the released flue gas; during combustion, the nickel-based MOF in the outer sheath... The highly active nano-NiO particles are generated by thermal decomposition and diffuse into the inner layer under the action of combustion temperature gradient and thermal convection. The inner layer ADP / boehmite core-shell powder is pyrolyzed to generate aluminum metaphosphate glass phase. The NiO particles diffused to the interface undergo solid-state reaction with the aluminum metaphosphate glass phase. Nickel ions are doped into the interior of the phosphate lattice, which can significantly increase the softening temperature and high-temperature melt viscosity of the phosphate glass phase, making it less prone to melting and dripping under the action of high-temperature flame, effectively suppressing the generation of combustion droplets, and improving the density of the carbon layer and the high-temperature structural stability. Attached Figure Description

[0026] Figure 1 Thermogravimetric analysis (TGA) curves of modified ADP powder.

[0027] Figure 2 This is a comparison of the Fourier transform infrared (FT-IR) spectra of the modified ADP powder before and after the reaction with MDI.

[0028] Figure 3 The images show physical photos of the prepolymerized ADP and a record of the reaction system's state.

[0029] Figure 4 This is a SEM image of the modified ADP powder.

[0030] Figure 5 SEM image of ADP / boehmite core-shell powder. Detailed Implementation

[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0032] Example 1: A method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable, comprising the following steps: S1: Add 10g ADP powder, 3g hydroxyethyl methacrylate and 0.5g ethylene glycol dimethacrylate to a reaction vessel and stir for 20min at 20℃ and 500r / min. Then add 0.4g Tween-80 and 1.2g Span-80, heat to 70℃ and continue stirring for 10min to form an oil phase mixture. Add 0.2g sodium dodecylbenzenesulfonate and 250mL deionized water to the reaction vessel and stir for 20min at 70℃ and 500r / min. Then add 15g oil phase mixture and 0.15g azobisisobutyronitrile and continue stirring for 4h. Centrifuge at 1000r / min for 4min, filter, wash the product twice with deionized water, and vacuum dry at 60℃ for 1h to obtain modified ADP powder.

[0033] Hydroxyethyl methacrylate (HME) is used as a functional monomer and ethylene glycol dimethacrylate (EDA) is used as a crosslinking monomer. Under the thermal initiation of azobisisobutyronitrile (AIBN), HME polymerizes and crosslinks on the surface of ADP particles to form a poly(hydroxyethyl methacrylate) coating layer. The HME coating layer has a large number of residual active hydroxyl groups, which provide reaction sites for subsequent polyurethane covalent grafting. At the same time, it improves the dispersibility of ADP in the matrix and inhibits particle agglomeration.

[0034] S2: 8g of modified ADP powder, 30g of 4,4'-diphenylmethane diisocyanate, and 0.05g of dibutyltin dilaurate were added to a reactor and stirred for 20min at 20℃ and 500r / min under a nitrogen atmosphere. The mixture was then heated to 80℃ and stirred for another 2h to obtain prepolymerized modified ADP. 6g of boehmite, 14g of 4,4'-diphenylmethane diisocyanate, and 0.02g of dibutyltin dilaurate were added to a reactor and heated to 80℃ under a nitrogen atmosphere. The mixture was stirred for another 2h to obtain prepolymerized modified boehmite. 6g of prepolymerized modified ADP, 4g of prepolymerized modified boehmite, and 2g of 1,4'-butanediol were added to a reactor and chain-extending reaction was carried out at 80℃ and 500r / min for 2h. The mixture was filtered, washed twice with deionized water, and vacuum dried at 60℃ for 1h to obtain ADP / boehmite core-shell powder.

[0035] Prepolymerized modified ADP and prepolymerized modified boehmite were prepared by adding 4,4'-diphenylmethane diisocyanate to the hydroxyl groups on the surface of modified ADP powder and boehmite, respectively, under the catalysis of dibutyltin dilaurate. The modified ADP core and prepolymerized modified boehmite were then chain-extended by 1,4-butanediol with the isocyanate groups at both ends of the prepolymerized modified ADP and prepolymerized modified boehmite, using polyurethane segments as covalent bridges to firmly connect the modified ADP core and the boehmite shell, forming a core-shell structure with modified ADP as the core and boehmite as the shell.

[0036] S3: 18g of nickel nitrate, 12g of 2,5-dihydroxyterephthalic acid and 800mL of N,N-dimethylformamide were added to a polytetrafluoroethylene hydrothermal reactor and stirred at 120℃ and 500r / min for 10h. After the reaction was completed, the mixture was centrifuged at 5000r / min for 5min. The precipitate was washed twice with N,N-dimethylformamide and anhydrous ethanol, respectively, and dried under vacuum at 60℃ for 1h to obtain nickel-based MOF.

[0037] S4: Mix 70g of low-density polyethylene, 10g of ADP / boehmite core-shell powder, 1g of ethylene bis-stearamide and 5.5g of wire core filler evenly and add them to a co-rotating parallel twin-screw extruder. Extrude at 180℃ and 180r / min and granulate to obtain modified low-density polyethylene masterbatch.

[0038] S5: Mix 70g of maleic anhydride-grafted high-density polyethylene, 10g of nickel-based MOF, 1g of ethylene bis-stearamide and 22.5g of sheath filler evenly and add them to a co-rotating parallel twin-screw extruder. Extrude at 180℃ and 180r / min and granulate to obtain modified high-density polyethylene masterbatch.

[0039] S6: Annealed soft copper monofilaments are concentrically stranded on a frame-type stranding machine or a tubular stranding machine at a pitch ratio of 14 to obtain the conductor core; a semi-conductive shielding material is used as the shielding layer, modified low-density polyethylene masterbatch is used as the insulation layer, and modified high-density polyethylene masterbatch is used as the sheath layer. These are then co-extruded with the conductor core using a three-layer co-extrusion process to achieve a tight, gapless wrapping of the insulation layer, sheath layer, and conductor, resulting in a low-smoke, high-temperature resistant polyolefin sheathed high-voltage cable.

[0040] Example 2: A method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable, comprising the following steps: S1: 11g ADP powder, 4g hydroxyethyl methacrylate and 0.6g ethylene glycol dimethacrylate were added to a reaction vessel and stirred for 25min at 22.5℃ and 550r / min. Then 0.5g Tween-80 and 1.35g Span-80 were added, and the mixture was heated to 75℃ and stirred for another 11min to form an oil phase mixture. 0.35g sodium dodecylbenzenesulfonate and 275mL deionized water were added to the reaction vessel and stirred for 25min at 72.5℃ and 550r / min. Then 15.5g of the oil phase mixture and 0.175g azobisisobutyronitrile were added, and the mixture was stirred for another 4.5h. After centrifugation at 1100r / min for 5min, the mixture was filtered, and the product was washed three times with deionized water and dried under vacuum at 65℃ for 1.5h to obtain modified ADP powder.

[0041] S2: Add 9g of modified ADP powder, 35g of 4,4'-diphenylmethane diisocyanate, and 0.06g of dibutyltin dilaurate to a reactor. Stir for 25min under a nitrogen atmosphere, at 22.5℃ and 550r / min, then heat to 85℃ and continue stirring for 3h to obtain prepolymerized modified ADP; Add 7g of boehmite, 16g of 4,4'-diphenylmethane diisocyanate, and 0.03g of dibutyltin dilaurate to a reactor. Heat to 85℃ under a nitrogen atmosphere and continue stirring for 3h to obtain prepolymerized modified boehmite; Add 7g of prepolymerized modified ADP, 5g of prepolymerized modified boehmite, and 3g of... 1,4'-Butanediol was added to a reaction vessel and subjected to chain extension reaction at 85℃ and 550 r / min for 2.5 h. After filtration, the product was washed three times with deionized water and dried under vacuum at 65℃ for 1.5 h to obtain ADP / boehmite core-shell powder.

[0042] S3: 19g of nickel nitrate, 13.5g of 2,5-dihydroxyterephthalic acid and 850mL of N,N-dimethylformamide were added to a polytetrafluoroethylene hydrothermal reactor and stirred at 125℃ and 550r / min for 11h. After the reaction was completed, the mixture was centrifuged at 5500r / min for 6.5min. The precipitate was washed three times with N,N-dimethylformamide and anhydrous ethanol, respectively, and dried under vacuum at 65℃ for 1.5h to obtain nickel-based MOF.

[0043] S4: Mix 75g of low-density polyethylene, 12.5g of ADP / boehmite core-shell powder, 1.5g of ethylene bis-stearamide and 6.95g of wire core filler evenly and then add them to a co-rotating parallel twin-screw extruder. Extrude at 182.5℃ and 185r / min and granulate to obtain modified low-density polyethylene masterbatch.

[0044] S5: Mix 75g of maleic anhydride-grafted high-density polyethylene, 11g of nickel-based MOF, 1.5g of ethylene bis-stearamide and 26.75g of sheath filler evenly and add them to a co-rotating parallel twin-screw extruder. Extrude at 182.5℃ and 185r / min, granulate, and obtain modified high-density polyethylene masterbatch.

[0045] S6: Annealed soft copper monofilaments are concentrically stranded on a frame-type stranding machine or a tubular stranding machine at a pitch ratio of 16 to obtain the conductor core; a semi-conductive shielding material is used as the shielding layer, modified low-density polyethylene masterbatch is used as the insulation layer, and modified high-density polyethylene masterbatch is used as the sheath layer. These are then co-extruded with the conductor core using a three-layer co-extrusion process to achieve a tight, gapless wrapping of the insulation layer, sheath layer, and conductor, resulting in a low-smoke, high-temperature resistant polyolefin sheathed high-voltage cable.

[0046] Example 3: A method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable, comprising the following steps: S1: 12g ADP powder, 5g hydroxyethyl methacrylate and 0.7g ethylene glycol dimethacrylate were added to a reaction vessel and stirred for 30min at 25℃ and 600r / min. Then 0.6g Tween-80 and 1.5g Span-80 were added, and the mixture was heated to 80℃ and stirred for another 12min to form an oil phase mixture. 0.5g sodium dodecylbenzenesulfonate and 300mL deionized water were added to the reaction vessel and stirred for 30min at 75℃ and 600r / min. Then 16g of the oil phase mixture and 0.2g azobisisobutyronitrile were added, and the mixture was stirred for another 5h. After centrifugation at 1200r / min for 6min, the mixture was filtered. The product was washed four times with deionized water and dried under vacuum at 70℃ for 2h to obtain modified ADP powder.

[0047] S2: 10g of modified ADP powder, 40g of 4,4'-diphenylmethane diisocyanate, and 0.07g of dibutyltin dilaurate were added to a reactor. The mixture was stirred for 30min under a nitrogen atmosphere at 25℃ and 600r / min, then heated to 90℃ and stirred for another 4h to obtain prepolymerized modified ADP. 8g of boehmite, 18g of 4,4'-diphenylmethane diisocyanate, and 0.04g of dibutyltin dilaurate were added to a reactor. The mixture was heated to 90℃ under a nitrogen atmosphere and stirred for another 4h to obtain prepolymerized modified boehmite. 8g of prepolymerized modified ADP, 6g of prepolymerized modified boehmite, and 4g of... 1,4'-Butanediol was added to a reaction vessel and subjected to chain extension reaction at 90℃ and 600 r / min for 3 h. After filtration, the product was washed four times with deionized water and dried under vacuum at 70℃ for 2 h to obtain ADP / boehmite core-shell powder.

[0048] S3: Add 20g nickel nitrate, 15g 2,5-dihydroxyterephthalic acid and 900mL N,N-dimethylformamide to a polytetrafluoroethylene hydrothermal reactor, and stir for 12h at 130℃ and 600r / min. After the reaction is completed, centrifuge at 6000r / min for 8min, wash the precipitate four times with N,N-dimethylformamide and anhydrous ethanol respectively, and dry it under vacuum at 70℃ for 2h to obtain nickel-based MOF.

[0049] S4: Mix 80g of low-density polyethylene, 15g of ADP / boehmite core-shell powder, 2g of ethylene bis-stearamide and 8.4g of wire core filler evenly and add them to a co-rotating parallel twin-screw extruder. Extrude at 185℃ and 190r / min and granulate to obtain modified low-density polyethylene masterbatch.

[0050] S5: Mix 80g of maleic anhydride-grafted high-density polyethylene, 12g of nickel-based MOF, 2g of ethylene bis-stearamide and 31g of sheath filler evenly and add them to a co-rotating parallel twin-screw extruder. Extrude at 185℃ and 190r / min and granulate to obtain modified high-density polyethylene masterbatch.

[0051] S6: Annealed soft copper monofilaments are concentrically stranded on a frame-type stranding machine or a tubular stranding machine at a pitch ratio of 18 to obtain the conductor core; a semi-conductive shielding material is used as the shielding layer, modified low-density polyethylene masterbatch is used as the insulation layer, and modified high-density polyethylene masterbatch is used as the sheath layer. These are then co-extruded with the conductor core using a three-layer co-extrusion process to achieve a tight, gapless wrapping of the insulation layer, sheath layer, and conductor, resulting in a low-smoke, high-temperature resistant polyolefin sheathed high-voltage cable.

[0052] Comparative Example 1: Based on Example 3, the ADP / boehmite core-shell powder in step S4 was replaced with the modified ADP powder prepared in step S2, while the other steps remained unchanged, to prepare a low-smoke, high-temperature resistant polyolefin sheathed high-voltage cable.

[0053] Comparative Example 2: Based on Example 3, the ADP / boehmite core-shell powder in step S4 was discarded.

[0054] Comparative Example 3: Based on Example 3, the nickel-based MOF in step S5 was omitted.

[0055] In the embodiments and comparative examples of this invention: ADP is aluminum diethylphosphonate, purchased from Hubei Xinghengye Technology Co., Ltd., CAS No.: 225789-38-8, molecular weight: 393.29.

[0056] The core filler consists of 2-3g pentaerythritol cyanoethylated, 1-2g nano silica, 0.5-0.7g dioctyl sebacate, 1.5-2g dicumyl peroxide, and 0.5-0.7g antioxidant 1010.

[0057] The sheath filler consists of 4-6g of high abrasion resistant carbon black N550, 5-6g of epoxidized soybean oil, 2-3g of calcium zinc stabilizer, 6-8g of poly(1,2-propanediol adipate), 1.5-2g of dicumyl peroxide, and 4-6g of dibutyl diglyceride adipate.

[0058] Hydroxyethyl methacrylate was purchased from Shandong Chuangying Chemical Co., Ltd., CAS No.: 868-77-9.

[0059] 4,4'-Diphenylmethane diisocyanate was purchased from Wuhan Jiyesheng Chemical Co., Ltd., CAS No.: 101-68-8.

[0060] Maleic anhydride-grafted high-density polyethylene was purchased from Dongguan Zhangmutou Yutao Plastic Raw Material Business Department.

[0061] The semiconductive shielding material was purchased from Ningjin County Haoxin New Material Technology Co., Ltd.

[0062] Performance tests were conducted on Examples 1-3 and Comparative Examples 1-3. The cantilever beam notched impact strength test was conducted according to GB / T1843-2008 standard. The smoke density test was conducted according to GB / T8323.2-2008 standard. The corrosion resistance test involved immersing the power cable samples in 20wt% sodium hydroxide solution and 20wt% sodium chloride solution under the same conditions for 168 hours, and then observing the surface corrosion.

[0063] High-voltage cable was prepared into a sample strip (100mm x 8mm x 3mm) and placed at 25℃ and 50% relative humidity for 120 hours. The sample strip was then vertically fixed in the center of a transparent glass combustion cylinder. The initial oxygen concentration was set to 45%. The oxygen and nitrogen sources were turned on, and the mixed gas was allowed to flow stably in the combustion cylinder for 30 seconds. The sample strip was ignited from the top using an igniter. The observation and recording of whether the sample strip continued to burn for more than 50mm was recorded. If it did, the oxygen concentration was reduced, and the next new sample was tested. If it did not, the oxygen concentration was increased, and the next new sample was tested. The above steps were repeated, and 15 data points of effective extinguishing were collected. The last 10 data points were used for calculation, referring to the standard GB / T2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test".

[0064] To test the tensile strength of a high-voltage cable, the specimen is prepared into a dumbbell shape, clamped on a universal testing machine, and stretched at a constant speed (500 mm / min) until it breaks. The maximum pressure is obtained, and its tensile strength is calculated.

[0065] Fire resistance time test of high-voltage cables: The sample is placed on the test frame and fixed at both ends. A static load plate is installed above the fire-exposed area in the middle of the sample, and a weight (cable outer diameter x 5 N / m) is applied. The vibration device is started (frequency 1 Hz, amplitude +5 mm), the test circuit is connected (voltage 1 kV), the blowtorch is started, and the flame center is aligned with the center of the fire-exposed area of ​​the sample. The time is recorded until one of the following indicators appears, indicating failure: current interruption in the test circuit, short circuit between the conductor and the load plate or ground, or the downward displacement of the static load plate exceeds 50% of the initial outer diameter of the cable. The results are shown in Table 1. Table 1 Performance Test Table for Low-Smoke, High-Temperature Resistant Polyolefin Sheathed High-Voltage Cables

[0066] As shown in Table 1, in Comparative Example 1, the physical barrier and char layer skeleton reinforcement of boehmite are lost. Relying solely on the gas-phase flame retardancy and condensation mechanism of ADP, the char layer is loose and prone to cracking during combustion, failing to effectively block oxygen and heat transfer. At the same time, the synergistic high-temperature stabilizing effect of NiO, boehmite, and phosphate glass phase is lacking, resulting in a significant reduction in refractory time and limiting oxygen index. Boehmite itself has a certain flue gas adsorption and solid-phase capture effect, and its absence leads to an increase in the release of flue gas and toxic gases during combustion, as well as an increase in smoke density. The interfacial bonding force between the single modified ADP and the polyethylene matrix is ​​weaker than that of the core-shell structure. Furthermore, without the compatibilization effect of polyurethane segments and the rigidity reinforcement effect of boehmite, the material is prone to embrittlement, a decrease in tensile strength, and the loss of the unique ball bearing effect of the core-shell structure, resulting in reduced melt fluidity. During extrusion, melt fracture and surface roughness are likely to occur, and the processing window becomes narrower.

[0067] In Comparative Example 2, the insulation layer contains no flame-retardant components. Pure low-density polyethylene is a flammable material that cannot form a char layer when burning. The flame spreads extremely quickly, and the fire resistance time is extremely short. Complete combustion of polyethylene will produce a large amount of black smoke and toxic and harmful gases. There is no dense char layer to block corrosive gases during combustion, and pure polyethylene itself has limited resistance to acid, alkali and salt corrosion. Significant corrosion will occur in sodium hydroxide and sodium chloride solutions. Although pure polyethylene melt has good fluidity, it lacks the reinforcing effect of core-shell powder on the interface, and the strength of the insulation layer and sheath layer is lower than that of the example.

[0068] In Comparative Example 3, the lack of nickel-based MOF as a Lewis acid catalyst to promote the dehydrogenation and crosslinking of the polyethylene matrix resulted in the inability to quickly form a dense and continuous char layer in the early stages of combustion. This led to an increase in the release of combustible gases, a decrease in the limiting oxygen index, and the absence of solid-phase reaction between NiO particles and the aluminum metaphosphate glass phase. The phosphate glass phase had a lower softening temperature and high-temperature melt viscosity, making it prone to melting and dripping under high-temperature flame conditions, which could easily trigger a secondary fire. The loss of the porous structure of the nickel-based MOF resulted in the physical adsorption of flue gas and toxic gases, leading to an increase in smoke density. The phosphate glass phase without nickel ion doping modification was prone to softening and collapse at high temperatures, failing to continuously block heat and oxygen, thus shortening the fire resistance time.

[0069] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable, characterized in that, Includes the following steps: Step 1: A poly(hydroxyethyl methacrylate) coating layer is formed on the surface of ADP powder by in-situ polymerization using reverse emulsion polymerization to obtain modified ADP powder. Using 4,4'-diphenylmethane diisocyanate as a bridge, prepolymerized modified ADP and prepolymerized modified boehmite are prepared by addition reaction of isocyanate groups and hydroxyl groups respectively. Then, through 1,4-butanediol chain extension reaction, boehmite is covalently bonded to the surface of modified ADP powder through polyurethane segments to obtain ADP / boehmite core-shell powder. Step 2: Low-density polyethylene, ADP / boehmite core-shell powder, ethylene bis-stearamide, and wire core filler are melt-blended, extruded, and granulated to prepare modified low-density polyethylene masterbatch; nickel-based MOF is prepared by hydrothermal synthesis and then melt-blended with maleic anhydride-grafted high-density polyethylene, ethylene bis-stearamide, and sheath filler, extruded, and granulated to prepare modified high-density polyethylene masterbatch; Step 3: Using semi-conductive shielding material as the shielding layer, modified low-density polyethylene masterbatch as the insulation layer, and modified high-density polyethylene masterbatch as the sheath layer, a three-layer co-extrusion process is adopted with the conductor core to achieve a tight, gapless wrapping of the insulation layer, sheath layer, and conductor, resulting in a low-smoke, high-temperature resistant polyolefin sheathed high-voltage cable.

2. The method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable according to claim 1, characterized in that, The specific preparation steps of the modified ADP powder are as follows: ADP powder, hydroxyethyl methacrylate, and ethylene glycol dimethacrylate were added to a reaction vessel and stirred at 20-25°C and 500-600 rpm for 20-30 min. Then, Tween-80 and Span-80 were added, and the mixture was heated to 70-80°C and stirred for another 10-12 min to form an oil phase mixture. Sodium dodecylbenzenesulfonate and deionized water were added to the reaction vessel and stirred at 70-75°C and 500-600 rpm for 20-30 min. Then, the oil phase mixture and azobisisobutyronitrile were added, and the mixture was stirred for another 4-5 h. The mixture was centrifuged at 1000-1200 rpm for 4-6 min, filtered, washed, and vacuum dried to obtain modified ADP powder. The mass ratio of ADP powder, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, Tween-80, and Span-80 is 10-12:3-5:0.5-0.7:0.4-0.6:1.2-1.

5. The ratio of sodium dodecylbenzenesulfonate, deionized water, oil phase mixture and azobisisobutyronitrile is 0.2-0.5g: 250-300mL: 15-16g: 0.15-0.2g.

3. The method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable according to claim 1, characterized in that, The specific preparation steps of the prepolymerized modified ADP are as follows: Modified ADP powder, 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate were added to a reaction vessel at a mass ratio of 8-10:30-40:0.05-0.

07. The mixture was stirred for 20-30 minutes under a nitrogen atmosphere, at 20-25°C and 500-600 r / min. The mixture was then heated to 80-90°C and stirred for another 2-4 hours to obtain prepolymerized modified ADP. The specific preparation steps for the prepolymerized modified boehmite are as follows: Boehmite, 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate were added to a reactor in a mass ratio of 6-8:14-18:0.02-0.

04. The mixture was heated to 80-90°C under a nitrogen atmosphere and stirred for 2-4 hours to obtain prepolymerized modified boehmite.

4. The method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable according to claim 1, characterized in that, The specific preparation steps for the ADP / boehmite core-shell powder are as follows: Prepolymerized modified ADP, prepolymerized modified boehmite, and 1,4'-butanediol were added to a reactor at a mass ratio of 6-8:4-6:2-4, and the reaction was carried out at 80-90℃ and 500-600 r / min for 2-3 h. The mixture was then filtered, washed, and vacuum dried to obtain ADP / boehmite core-shell powder.

5. The method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable according to claim 1, characterized in that, The specific preparation steps of the nickel-based MOF are as follows: Nickel nitrate, 2,5-dihydroxyterephthalic acid and N,N-dimethylformamide were added to a polytetrafluoroethylene hydrothermal reactor and stirred at 120-130℃ and 500-600 r / min for 10-12 h. After the reaction was completed, the mixture was centrifuged at 5000-6000 r / min for 5-8 min, washed, and vacuum dried to obtain nickel-based MOF. The ratio of nickel nitrate, 2,5-dihydroxyterephthalic acid, and N,N-dimethylformamide is 18-20g: 12-15g: 800-900mL.

6. The method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable according to claim 1, characterized in that, The specific preparation steps of the modified low-density polyethylene masterbatch are as follows: Low-density polyethylene, ADP / boehmite core-shell powder, ethylene bis-stearamide and wire core filler are mixed evenly and then added to a co-rotating parallel twin-screw extruder. The mixture is extruded at 180-185℃ and 180-190r / min and granulated to obtain modified low-density polyethylene masterbatch. The mass ratio of the low-density polyethylene, ADP / boehmite core-shell powder, ethylene bis-stearamide, and core filler is 70-80:10-15:1-2:5.5-8.

4.

7. The method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable according to claim 6, characterized in that, The core filler consists of 2-3g pentaerythritol cyanoethylated, 1-2g nano silica, 0.5-0.7g dioctyl sebacate, 1.5-2g dicumyl peroxide, and 0.5-0.7g antioxidant 1010.

8. The method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable according to claim 1, characterized in that, The specific preparation steps of the modified high-density polyethylene masterbatch are as follows: Maleic anhydride-grafted high-density polyethylene, nickel-based MOF, ethylene bis-stearamide and sheath filler are mixed evenly and then added to a co-rotating parallel twin-screw extruder. The mixture is extruded at 180-185℃ and 180-190r / min and granulated to obtain modified high-density polyethylene masterbatch. The mass ratio of maleic anhydride-grafted high-density polyethylene, nickel-based MOF, ethylene bis-stearamide, and sheath filler is 70-80:10-12:1-2:22.5-31.

9. The method for preparing a low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable according to claim 8, characterized in that, The sheath filler is composed of 4-6g of high abrasion resistant carbon black N550, 5-6g of epoxidized soybean oil, 2-3g of calcium zinc stabilizer, 6-8g of poly(1,2-propanediol adipate), 1.5-2g of dicumyl peroxide and 4-6g of dibutyl diglyceride adipate.

10. A low-smoke, high-temperature resistant polyolefin-sheathed high-voltage cable, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • A low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable

    CN118652489B